SISTEM INFORMASI PEMESANAN PAKET WISATA NAGARI TARUSAN KABUPATEN PESISIR SELATAN - Nofriadi man (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2016)
Nagari Tarusan located in the Kabupaten Pesisir Selatan which has many tourist resorts, culinary and traditions still hold in high regard. The tourist resorts has a great potential to be developed, but a high potential is still not supported by ease of access to reach the tourist site, where the number and frequency of departure public transportation to tourist objects that exist in the region is still low and not optimal. Making the reservation website Nagari Tarusan tour packages will provide convenience for the people of Indonesia and the world. With the tour package booking website Nagari Tarusan will promote local economies and provide additional income for the Kabupaten Pesisir Selatan budget later. Keywords : Website, Tourism